Correlation of Self Esteem and Students Academic Achievement in Physical Education Learning in the Covid-19 Period - bangbang syamsudar (aksararaga, 2022)
This study aimed to decscribe the correlation between self-esteem and academic achievement of students in physical education learning during Covid-19 pandemic era. Descriptive correlation with sampling technique used as the method of the research. Sample of the research is 32 tenth grade students at SMK Bunga Persada Cianjur. In collecting the data, Rosenberg Self-Esteem Scale was distributed to the students consisted of ten statement questions. While, students' report cards. The result revealed that there was a strong correlation between self-esteem and students' academic achievement.   Keywords: Self Esteem, Prestasi Akademik, Physical Education